Serum Protein N-Glycosylation Changes with Rheumatoid Arthritis Disease Activity during and after Pregnancy - Reiding, Karli R.; Vreeker, Gerda C. M.; Bondt, Albert; Bladergroen, Marco R.; Hazes, Johanna M. W.; van der Burgt, Yuri E. M.; Wuhrer, Manfred; Dolhain, Radboud J. E. M. (Frontiers in Medicine, 2018)
Symptoms of rheumatoid arthritis (RA) improve during pregnancy, a phenomenon that was found to be associated with N-glycosylation changes of immunoglobulin G (IgG). Recent advances in high-throughput glycosylation analysis allow the assessment of the N-glycome of human sera as well. The aim of this study was to identify new protein N-glycosylation properties that associate with changes in RA disease activity during and after pregnancy. A longitudinal cohort of serum samples was collected during 285 pregnancies (32 control individuals and 253 RA patients). Per individual one sample was collected before conception, three during pregnancy, and three after delivery. Released serum protein N-glycans were measured by matrix-assisted laser desorption/ionization mass spectrometry (MALDI-TOF-MS) after employing chemical modification of the sialic acids to allow discrimination of sialic acid linkage isomers. Serum protein N-glycosylation showed strongly modified during pregnancy, with similar changes visible in control individuals and RA pregnancies. Namely, a decrease in bisection and an increase in galactosylation in diantennary glycans were found, as well as an increase in tri- and tetraantennary species and α2,3-linked sialylation thereof. The change in RA disease activity (DAS28(3)-CRP) proved negatively associated with the galactosylation of diantennary N-glycans, and positively with the sialylation of triantennary fucosylated species (A3FGS). While the protein source of the novel finding A3FGS is thus far unknown, its further study may improve our understanding of the etiology of RA disease severity.